The world in a book : Al-Nuwayri and the Islamic encyclopedic tradition - Muhanna, Elias (Princeton University Press, 2018)
Shihab al-Din al-Nuwayri was a fourteenth-century Egyptian polymath and the author of one of the greatest encyclopedias of the medieval Islamic world-a thirty-one-volume work entitled The Ultimate Ambition in the Arts of Erudition. A storehouse of knowledge, this enormous book brought together materials on nearly every conceivable subject, from cosmology, zoology, and botany to philosophy, poetry, ethics, statecraft, and history. Composed in Cairo during the golden age of Islamic encyclopedic activity, the Ultimate Ambition was one of hundreds of large-scale compendia, literary anthologies, dictionaries, and chronicles produced at this time-an effort that was instrumental in organizing the archive of medieval Islamic thought. In the first study of this landmark work in a European language, Elias Muhanna explores its structure and contents, sources and influences, and reception and impact in the Islamic world and Europe. He sheds new light on the rise of encyclopedic literature in the learned cities of the Mamluk Empire and situates this intellectual movement alongside other encyclopedic traditions in the ancient, medieval, Renaissance, and Enlightenment periods. He also uncovers al-Nuwayri's world: a scene of bustling colleges, imperial chanceries, crowded libraries, and religious politics. Based on award-winning scholarship, The World in a Book opens up new areas in the comparative study of encyclopedic production and the transmission of knowledge.